Maqâmat al-Sâlik li al-Wushȗl Ila al-Khâliq (Ringkasan Kitab Minhâj al-‘Abidîn Ilâ Jannati Rabbil ‘Alamîn) Karya Hujjatul Islam Imam al-Ghazali - Dahri, Haji Harapandi (IAIN Samarinda, 2018)
Every man wants to be close to God as Creator, even though not conscious, humans long for His presence every moment especially when getting difficulty and tiredness, longing to be close to Him is nature. Hujat al-Islam Imam al-Ghazali never felt the same, because that is what he poured great ideas, method of finding and approaching the real Maha close in a work given the title